We have,

x−y=-2----1

3x−y=−2----2

From equation (1), we get the value of x in terms of y as

x−y=−2

x=y−2 ⋯⋯(3)

On substituting the value of x=y−2 from equation (3) to equation (2), we get the value of y as

3(y−2)−y=-2

3y−6−y=-2

2y=4

y=2

Now substitute value of y=2 in equation (3), we get value of x as

x=2−2

x=0

Hence, (0,2) is an ordered pair of solution, not the (1,3).

x−y=-2----1

3x−y=−2----2

From equation (1), we get the value of x in terms of y as

x−y=−2

x=y−2 ⋯⋯(3)

On substituting the value of x=y−2 from equation (3) to equation (2), we get the value of y as

3(y−2)−y=-2

3y−6−y=-2

2y=4

y=2

Now substitute value of y=2 in equation (3), we get value of x as

x=2−2

x=0

Hence, (0,2) is an ordered pair of solution, not the (1,3).